Techno-Economic Analysis of Photovoltaic Systems Integrated with Geothermal Energy for Poultry Housing in El Oued Climate Conditions - Yahia Dou; Saned Ayadi Saad Eddine Lachheb; Saad Eddine Lachheb (University of Shahid Hama Lakhdar - El Oued, 2025)
"This study investigates the integration of renewable energy technologies, particularly geothermal and solar energy, into poultry housing systems in arid regions, with a focus on El Oued, Algeria. The research aims to develop and assess a geothermal HVAC system tailored for broiler chicken farms, promoting energy efficiency, improved animal welfare, and economic viability. A comprehensive review of poultry housing requirements, thermal comfort, ventilation strategies, and environmental stressors—such as heat stress—was conducted. The study compares traditional and modern poultry systems, emphasizing the advantages of hybrid renewable energy systems (HRES) combining solar photovoltaic and geothermal energy. The system design includes photovoltaic sizing, geothermal heat pump implementation, and ventilation optimization. Field data from local poultry farms inform the analysis, revealing substantial performance gains, reduced mortality, and enhanced productivity in modern facilities. Results suggest that adopting HRES in poultry farming can significantly reduce reliance on fossil fuels, lower operational costs, and contribute to sustainable agriculture in desert climates." "تتناول هذه الدراسة دمج تقنيات الطاقة المتجددة، وخصو ًصا الطاقة الحرارية الجوفية والطاقة الشمسية، في أنظمة إسكان الدواجن في المناطق الجافة، مع التركيز على منطقة الوادي في الجزائر. يهدف البحث إلى تطوير وتقييم نظام تدفئة وتهوية وتكييف (HVAC (يعمل بالطاقة الجوفية ومخصص لمزارع دجاج ، وذلك لتعزيز كفاءة استخدام الطاقة، وتحسين جودة الدواجن ، وزيادة الجدوى االقتصادية. تم إجراء مراجعة شاملة لمتطلبات إسكان الدواجن، استراتيجيات التهوية والعوامل البيئية الضاغطة مثل اإلجهاد الحراري. كما تم إجراء مقارنة بين األنظمة التقليدية والحديثة في تربية الدواجن، مع إبراز مزايا أنظمة الطاقة المتجددة الهجينة (HRES(التي تجمع بين الطاقة الشمسية الكهروضوئية والطاقة الجوفية. يشمل تصميم النظام تحديد حجم األلواح الشمسية، وتطبيق مضخة حرارية جوفية، وتحسين نظام التهوية. وقد استُخدمت بيانات ميدانية من مزارع دواجن محلية في التحليل، مما أظهر تحسنًا كبي ًرا في األداء، وانخفا ًضا في معدل النفوق، وزيادة في اإلنتاجية في المنشآت الحديثة. وتشير النتائج إلى أن اعتماد أنظمة الطاقة المتجددة الهجينة في تربية الدواجن يمكن أن يقلل بشكل كبير من االعتماد على الوقود األحفوري، ويساهم في الزراعة المستدامة في المناخات الصحراوية. "
Master's thesis in electromechanics.2025
Keywords: HVAC: Heating Ventilation and Air Conditioning. IEA: International Energy Agency. HRES: Hybrid Renewable Energy Systems. PV/T: photovoltaic/thermal. EAHE: Earth Air Heat Exchangers. WTO: World Trade Organization.; التدفئة والتهوية وتكييف الهواء. الوكالة الدولية للطاقة. أنظمة الطاقة المتجددة الهجينة. الطاقة الكهروضوئية/الحرارية. المبادلات الحرارية الأرضية/الهواءية. منظمة التجارة العالمية.